SPIA Uganda Report 2025: Agricultural Diversity Under Stress - Ilukor, J.; Letaa, E.; Khanal, A.; Barros, J.; Taye, L; Gimode, D.; Ponzini, G.; Asea, G.; Ssennono, V.; Stevenson, James R.; Lybbert, T.; Macours, K. (2025)
First Version, SPIA Uganda Report 2025: Agricultural Diversity Under Stress